Negative Transfer as Linguistic Challenges in Islamic Boarding School Students' Writing - Wulandari, Sri; Nursari, Diniyah Laita; nashiroh, annis satu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2025)
This research was motivated by a phenomenon of grammatical interference that occurred at the Islamic Boarding School using English students in daily conversation. The purpose of this research was to find out the form and factors of grammatical interference produced by students of Al-Madienah. This research used descriptive qualitative methods. Fifty-five resource persons were taken consisting of the students of 11th grade of Al-Madienah Islamic Boarding School. Data collection in this research was carried out in three ways: interviews, observation, and documentation. For the instruments used in data collection, there are three instruments, there are interview guides, observation checklists, and a list of documentation. Data analysis was carried out according to the theory of Miles and Hubermen (1992): data reduction, data display, and verification. The results of the data analysis are: 1) Pronouns and syntactic interference are the two types of grammatical interference in Al-Madienah. 2) Bilingualism and the decline in speakers' primary language are the two reasons that create grammatical interference. Grammatical interference always appears in communities that speak another language because bilingualism will happen when people speak in two languages or more and bilingualism is the big factor causing interference.